Efek Anti Oksidan Bawang Putih terhadap Penurunan Bilangan Peroksida Minyak Jelantah - Siti Mardiyah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
Used cooking oil is leftover cooking oil from food frying processes. The use of cooking oil which is repeated with a high temperature and a long time can cause the oil to oxidation and hydrolysis, resulting in increased levels of peroxide. High peroxide value can pose a health hazard. Allisin is antioxidants contained in garlic. Allisin are primary antioxidants which act as free radical scavengers that can slow oxidation on used cooking oil. The purpose of this study was to determine the effect of garlic on decreased levels of peroxide in used cooking oil. This type of research is experimental by the number of samples in each treatment as many as 4 samples. Formulation of the problem of this study is whether there is the effect of adding garlic to decreased levels of peroxide on used cooking oil.From the results of the average levels of peroxide in used cooking oil that has been saved within 3 days is 26.0482 control mEq, 10 mEq% 23.65098, 22.71355 mEq 20%, 30% mEq 18.65023, 17.92128 mEq 40%, 50% 16.52508 mEq. Statistical analysis with ANOVA test shows the effect of adding garlic to decreased levels of peroxide in used cooking oil with p value (sig) = 0.000 which is smaller than 0.05. The results of Tukey HSD test showed the addition of garlic 30% is effective to reduce levels of peroxide on used cooking oil.Therefore, the addition of garlic may inhibit the process of rancidity and lower levels of peroxide in used cooking oil.KEYWORDS: garlic, cooking oil, peroxide value